Study of high emittance chemical conversion coatings for magnesium alloys. (January 2014) - Liu, Q. L.; Wang, X. D.; Wang, X. K.; Yan, X. W.; Ma, X. J.
<x content-type="archive" xml:space="preserve">Abstract</x> Comparative studies on five black chemical conversion coatings for magnesium alloy ZK60A have been conducted. The surface morphology and composition of the coatings were examined by SEM and energy dispersive spectroscopy techniques. The electrochemical and damp heat tests were conducted to examine the resistance of the coatings to corrosive prelaunch and launch conditions. The hemispherical emittance was measured to evaluate their worthiness of the application in aerospace industry. An optimum process condition, which provided a coating with satisfactory corrosion resistance and hemispherical emittance of 0·92, was determined. The formation mechanism and influence factors on the properties of the coatings were also discussed.